Technology Readiness of Smart Human Resource Management in Malaysia - Luqmanuhakim Kadir Hussein; Nor Hazana Abdullah (Research in Management of Technology and Business, 2023)
SMART human resource management is a software system that organises, and processes precise employee information and human resources linked to policies and procedures. The present human resource system is claimed to be slow, time consuming and lacks device capabilities that cause insufficient process for employees. The study aimed to measure the level of SMART human resource management implementation in Malaysia and the level of technology readiness among companies in Malaysia. This study employed quantitative research methods, using descriptive questionnaires to collect the data. The data will be analysed using measures of tendency and measure of dispersion. Data will be also tabulated using means to determine the level of readiness and implementation. This finding is expected to add to empirical repository of technology readiness literatures and to gauge the extent of Malaysian companies’ readiness to use SMART HRM.